Participatory evaluation of provitamin a-rich maize (zea mays l.) hybrids in savanna zones of northeast Nigeria - Dugje, I. Y.; Menkir, A.; Kamai, N.; Aminu, D.; Kamara, A. Y.; Odo, P. E.; Teli, I. A. (University of Abuja, 2021)
Field studies were conducted to assess the adaptability of Provitamin-A rich maize hybrids across farmer locations in Sudan (SS), Northern Guinea (NGS) and Southern Guinea Savannas (SGS). Six intermediate maturing maize hybrids, one Improved and one Local Check were laid out in a randomized complete block design and the treatments replicated 4 times in each site. Plant height was negatively correlated with Anthesis Silking Intervals (ASI) and grain yield/ha (r = - 0.26***). Ear heights were positively associated with plant height but negatively correlated with ASI. There was a delay of 5 and 6 days each in period to taselling in SS compared to the NGS and SGS. Days to tasseling was negatively associated with ASI across the zones and for the Ecologies Combined (EC)(r = - 0.56***). LY0902-12, LY0902-18, LY0906-8 significantly attained period to silking earlier than LY0614-8, LY0614-11 and LY0902-19 across the 3 ecologies and days to silking were potitively correlated with days to tasselling for EC (r = 0.83***). Shorter ASI were observed for LY0902-19, LY0902-18, LY0906-8 and LY0614-11 than LY0614-8. Grain yield of promising hybrids increased: LY0614-8 > LY0906-8 > LY0902-19 > LY0614-11. Farmer preferred traits are high yield, quality nutrient, Striga tolerance, early maturity and drought tolerance. Introduction of maize hybrids with these traits and shorter plants than those tested will improve maize productivity and enhance nutrition in the region.